“Regional blocks of ABS”: how the blockchain technology could enable a regional solution to transboundary situations - Dayana de Carvalho Uhdre; Giovanna Gruber (Revista de Direito Econômico e Socioambiental)
The evolution of consumption habits, in search of more natural products, increasingly requires the use of genetic resources to satisfy the demands of society. Considering that many of these resources come from transboundary species and that access to them and their use in research and technological development is primarily regulated by international ABS regimes, the article exposes some of the limits of international standards, especially the Nagoya Protocol, when dealing with these situations in particular, identifying the intention in the elaboration of the regimes. Based on this analysis, a regional solution is proposed, allied to the existing trend towards the elaboration of norms at this level of governance, in order to ensure the effectiveness of the regimes. To implement this solution, the use of blockchain technology is suggested to create distributed platforms that can serve different countries, traditional peoples and users involved in activities with genetic resources and associated traditional knowledge. The technology allows for greater transparency, traceability and decentralization of data, in addition to allowing automation and cost reduction of several operations, among other attributes, although it is not free of limits, challenges and criticisms.